Peningkatan Aktivitas dan Hasil Belajar Siswa melalui Pembelajaran Matematika Realistik - Maryam, Siti (Jurnal Ilmiah IKIP Mataram, 2023)
The purpose of this research is to increase students’ activities and learning outcomes through Realistic Mathematics Learning. The research method used is Classroom Action Research with reference to Kemmis & McTaggrat. The research was carried out on fifth grade students of SD Negeri Pakuniran I, Pakuniran District, Probolinggo Regency, in the odd semester of the 2021/2022 academic year. The results showed that there was an increase in student activity and learning outcomes in cycles 1 and 2 with the implementation of Realistic Mathematics Learning. The application of learning is carried out by the teacher using contextual problems related to the material to start learning, students experiencing directly the problem of fractions, students discussing fractions based on the worksheets they receive, finding concepts based on the results of discussions and then introducing standard procedures to solve problems using formulas and in learning. Â